2022
DOI: 10.1111/cns.14031
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐binding protein DHX9 promotes glioma growth and tumor‐associated macrophages infiltration via TCF12

Abstract: Background: Glioma is the most common malignant tumor of the central nervous system, with high heterogeneity, strong invasiveness, high therapeutic resistance, and poor prognosis, comprehending a serious challenge in neuro-oncology. Until now, the mechanisms underlying glioma progression have not been fully elucidated. Methods:The expression of DExH-box helicase 9 (DHX9) in tissues and cells was detected by qRT-PCR and western blot. EdU and transwell assays were conducted to assess the effect of DHX9 on prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The expression of the RNA helicase in various tissues is different, and the expression in different varieties of sweetpotato is also quite different. This also shows that the RNA helicase is related to growth and development (Tyagi et al, 2020;Liu et al, 2023). Some the RNA helicase genes were highly communicated in stems and roots of sweetpotato, such as IbDExDH25, IbDEAH42, IbDExDH47, and IbDExDH96.…”
Section: Rna Helicase Family Of Different Sweet Potato Cultivarsmentioning
confidence: 70%
“…The expression of the RNA helicase in various tissues is different, and the expression in different varieties of sweetpotato is also quite different. This also shows that the RNA helicase is related to growth and development (Tyagi et al, 2020;Liu et al, 2023). Some the RNA helicase genes were highly communicated in stems and roots of sweetpotato, such as IbDExDH25, IbDEAH42, IbDExDH47, and IbDExDH96.…”
Section: Rna Helicase Family Of Different Sweet Potato Cultivarsmentioning
confidence: 70%
“…Targeting M2 TAMs in TME is considered as an potential effective therapeutic strategy against cancer 27 . Our previous studies have found that GBM could promote glioma‐associated macrophage infiltration and M2 polarization 28 . Exosomes are membrane‐enclosed extracellular vesicles carrying biomolecules that include proteins and nucleic acids, especially miRNAs 16 .…”
Section: Discussionmentioning
confidence: 99%
“…27 Our previous studies have found that GBM could promote glioma-associated macrophage infiltration and M2 polarization. 28 Exosomes are membrane-enclosed extracellular vesicles carrying biomolecules that include proteins and nucleic acids, especially miRNAs. 16 In the current studies, we explored the effects and underlying mechanisms of cosstalk between GSCs and macrophages on M2 polarization, which disclosed that GSCs-derived exosomal miR-6733-5p can induce M2 macrophage polarization, and polarized M2 macrophages promote F I G U R E 2 Glioblastoma stem cells (GSCs)-exo induces M2 macrophage polarization.…”
Section: Discussionmentioning
confidence: 99%
“…Ndufs1 (NADH:Ubiquinone Oxidoreductase Core Subunit S1; UniProt P28331) is involved in the adaptability of tumor cells to their environment, particularly at low pH 64 . Furthermore, Dhx9 , Dusp12 , Fhl1 , and Ifitm1 are each correlated with the invasion of tumor‐infiltrating immune cells into the microenvironment 59,65–67 . In contrast, Pja2 (Praja Ring Finger Ubiquitin Ligase 2; UniProt O43164) promotes anti‐cancer M1 macrophage polarization 68 .…”
Section: Discussionmentioning
confidence: 99%